English Teachers in France and Facebook: Use and Professional Growth - karine LONGIS MCMILLAN (Journal of Educational, Health and Community Psychology, 2020)
AbstractDoes Facebook have an effect on English teachers in France? For this, a group of 85 secondary school English teachers in France aged 21 to 50+ were recruited from Facebook’s English teacher groups and answered an online questionnaire on their usages and practices. We observed no differences as regards to age and frequency of use, no effect between the number of associations to English teachers’ groups and professional growth, no significant relationship between the amount of participation and support used and professional growth in time, finally, sharing lessons online was a significant predictor of how some English teachers help others grow professionally. Regrettably, this study was limited to only a few groups. Thus, investigating the use of SNS in a broader context could open the possibility for the development of future research on this field.Keywords: Facebook, English teachers, France, practices